(untitled) (Journal of Philosophy Culture and Political Science, 2018)
It has been believed that stable foundation of society had been from the ability to reason of human beings. However, the identity of individuals in modern society is being fragmented. In the late 20th century the emergence of postmodernistic identity is shaking the framework of modern society.